Cognitive-reflective component of research competence of future higher education institution teachers - Grytsan, Oleksandr (ScienceRise: Pedagogical Education, 2026)
The article examines the problem of forming research competence of future teachers of higher education institutions in the context of socio-cultural and educational challenges. The relevance of the outlined issues is due to the need for a thorough study of the influence of cognitive and reflective processes on the development of key and professional competencies of future teachers of higher education institutions, their cognitive styles, ways of thinking on the processes of intensification of the acquisition of knowledge, skills, and abilities during learning and teaching in the conditions of digitalization of technologies and society, and the organization of scientific and research work. The typology of views and approaches to the nature and essence of the cognitive-reflective component in the structure of research competence of future teachers of higher education institutions is considered. The essence, component composition and features of the formation of the cognitive-reflective component of research competence for training a new generation of teachers of higher education institutions with a high level of research culture and critical thinking are analyzed. The cognitive and metacognitive skills, reflective abilities of a future teacher of a higher education institution, necessary for the organization and conduct of scientific and research activities, are described. It is substantiated that the quality and result of scientific and research activities directly correlate with the cognitive styles of the individual as individual ways of collecting, organizing, processing, systematizing, categorizing, and interpreting information using various research strategies. Cognitive flexibility is defined as one of the basic competencies of a future specialist, an integral component of his professional competence